DNA metabarcoding reveals distinct trophic niches among sympatric aerial insectivores (Family: Apodidae and Hirundinidae) in central Peninsular Malaysia - Fatihah Najihah Arazmi; Nor Adibah Ismail; Ummi Nur Syafiqah Daud; Mohammad Saiful Mansor (Nature Conservation)
Understanding the dietary preferences of aerial insectivores is essential for assessing their ecological roles in ecosystem energy flow. Despite this importance, few integrative studies have examined dietary overlap and niche segregation among coexisting aerial insectivore species, particularly in human-modified mosaic landscapes. This study addresses that gap by analysing the diets of four aerial insectivorous bird species: Apodidae, the House Swift (Apus nipalensis), House-farmed Swiftlet (Aerodramus sp.), Hirundinidae, the Barn Swallow (Hirundo rustica), and Pacific Swallow (Hirundo tahitica), within an urban–agricultural forest interface in central Peninsular Malaysia. A total of 60 faecal samples were collected over a one-week period in March 2022 and analysed using high-throughput sequencing of the mitochondrial COI gene. The results revealed arthropod prey from 13 orders, 97 families, 93 genera, and 65 species. Common prey orders included Hymenoptera, Diptera, and Coleoptera. Dietary diversity was highest in H. rustica indicating a generalist foraging strategy, while A. nipalensis showed the lowest prey richness and a more specialised diet. The varied dietary patterns among sympatric species and the dietary diversity reflect trophic niche partitioning and highlight the functional role of aerial insectivores in natural pest regulation. Ongoing environmental changes, particularly urbanisation, habitat fragmentation, and declining insect populations due to pesticide use pose growing threats to aerial insectivores. These findings highlight the need to conserve insect-rich habitats within mixed-use landscapes and support the application of metabarcoding as a tool for monitoring ecosystem health and guiding biodiversity-friendly land-use planning.